A desproteção da infância no sudoeste do Paraná: tecnologia como ferramenta de implementação da política pública para a infância (2009-2015) - Jubelli, Cleucimara Molon (2024)
This research analyzes data from the ten largest municipalities in the Southwest of the state of Paraná, covering the years 2009-2015, with the aim of verifying the violation of the rights to family and community coexistence of children and adolescents. The study of childhood and the historical space it occupied over the centuries, in addition to conceptual understanding, seeks to instigate reflections on the situation, the construction of legal systems and the concept of childhood feelings. In Brazil, ethnic-racial, social, cultural and religious influences characterized its conceptualization. Furthermore, it aims to understand childhood in contemporary times, a moment in which it is seen as a phase that requires care and concern, safeguarded from the attention of the family, the State and society. Furthermore, it analyzes public policies for children and adolescents with regard to rights violations in the Southwest region of Paraná, through statistical, social, economic and cultural diagnosis, providing indices and characteristics of the municipalities researched. Therefore, the history of childhood in Brazil was analyzed, the social problem arising from the difficulty of services meeting the needs of the child and youth population, the questions about the absolute priority and the essential legislative updates so that the fundamental rights, established in the Child Statute and of the Adolescent (ECA), were ensured, mainly the right to family and community life, the focus of the research. Furthermore, within the space-time framework, the importance of diagnosis and rates of violated rights to family and community coexistence in the municipalities researched was verified. In this context, the present study analyzed the child care policy, in order to verify, through data from the Information System for Children and Adolescents, with public access, the data belonging to the ten municipalities in the Southwest of the state of Paraná that belong to to the Francisco Beltrão region. It was possible to conclude that there are structural needs, but that the formation and adequate data supply generate impacts on the child and adolescent protection policy. It was also found that underreporting makes it difficult to monitor and evaluate existing public policies in the municipalities in scope.